2017
DOI: 10.1186/s12985-017-0798-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of illegal waste sites on a transmission of zoonotic viruses

Abstract: BackgroundIllegal waste disposal impacts public health and causes aesthetic and environmental pollution. Waste disposed in places without permitted and controlled facilities can provide a ready source of nutrition and shelter for rodents and thus promote the spread of their ecto- and endoparasites. The presence of two distinct zoonotic viruses, lymphocytic choriomeningitis virus (LCMV) and tick-borne encephalitis virus (TBEV), was searched at illegal waste sites. The aim of this study was to determine the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Several studies showed the impact of illegal waste sites on vector-borne diseases such as dengue [ 25 ], rodent-borne diseases such leptospirosis [ 26 ], toxoplasmosis [ 27 ], and zoonotic viruses [ 28 ]. However, few studies linking illegal waste and leishmaniasis have been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed the impact of illegal waste sites on vector-borne diseases such as dengue [ 25 ], rodent-borne diseases such leptospirosis [ 26 ], toxoplasmosis [ 27 ], and zoonotic viruses [ 28 ]. However, few studies linking illegal waste and leishmaniasis have been performed.…”
Section: Discussionmentioning
confidence: 99%
“…At waste sites, there are large quantities of organic waste that attract different vermin animals, particularly rodents. Results have shown that the transmission of other zoonotic pathogens between rodent species collected on waste sites, such as lymphocytic choriomeningitis virus, can be significantly increased by the presence of waste sites (53.33% in illegal waste sites vs. 17.39% in natural habitats) [7]. A study from Mexico showed that local rodent species have a relatively important role in the sylvatic cycle of T. gondii.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the existing infrastructure for dealing with waste, studies have revealed an extensive network of illegal waste sites [19] across Europe. These sites provide a ready source of nutrition and shelter for human-introduced rodents [4] that support the spread of pathogen vectors and non-native/invasive species [25] along the Mediterranean coast [7,14]. The higher parasitism and infection rates of animals in illegal waste sites could be significantly associated with the change in the rodent communities due to potential increase of commensal rodents brought there by human waste [4].…”
Section: Introductionmentioning
confidence: 99%
“…Leachate, complex mixture of organic, inorganic and many unidentified toxicants, may pose risk of unknown magnitude to aquatic life (Nwabueze, 2011). There are serious health implications due to the presence of illegal waste dumpsites in public places and lack of proper solid waste management (Duh et al, 2017). The flow of leachate from waste dumpsites into nearby water bodies and also percolation into soil may have adverse effect on aquatic organisms as well as plant growths.…”
Section: Discussionmentioning
confidence: 99%